2013
DOI: 10.1371/journal.pone.0070817
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Variations in the Glutamate Receptor, N-Methyl D-Aspartate 2A (GRIN2A) Gene Reveals Their Relative Importance as Genetic Susceptibility Factors for Heroin Addiction

Abstract: The glutamate receptor, N-methyl D-aspartate 2A (GRIN2A) gene that encodes the 2A subunit of the N-methyl D-aspartate (NMDA) receptor was recently shown to be involved in the development of opiate addiction. Genetic polymorphisms in GRIN2A have a plausible role in modulating the risk of heroin addiction. An association of GRIN2A single-nucleotide polymorphisms (SNPs) with heroin addiction was found earlier in African Americans. To identify markers that contribute to the genetic susceptibility to heroin addicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…Several single nucleotide polymorphisms (SNPs) have been identified in this gene, including rs3219790 in the promoter region (Itokawa et al, 2003a) and rs1014531, rs8044472, rs8045712, rs9933624, rs9940680, rs1420040, and rs767749 in the 3'-untranslated region (UTR) (Zhao et al, 2013). Itokawa et al (2003a) identified a variable (GT)n repeat (rs3219790) in the 5'-regulatory region.…”
Section: Introductionmentioning
confidence: 99%
“…Several single nucleotide polymorphisms (SNPs) have been identified in this gene, including rs3219790 in the promoter region (Itokawa et al, 2003a) and rs1014531, rs8044472, rs8045712, rs9933624, rs9940680, rs1420040, and rs767749 in the 3'-untranslated region (UTR) (Zhao et al, 2013). Itokawa et al (2003a) identified a variable (GT)n repeat (rs3219790) in the 5'-regulatory region.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have revealed the correlation of GRIN2A haplotypes i.e., rs4587976-rs1071502-rs1366076 (G-A-T) (13), rs837697, rs2650427, rs1969060, rs2937030, rs17682940, rs10500373, and rs11642357 (G-C-T-C-C-T-A) and rs1102972 and rs7499321 (T-T) [15] with heroin addiction. The present study also observed strong linkage disequilibrium and haplotype analyses revealed three SNPS (rs1071502-rs1366076-rs1104068) with alleles A-T-A (risk) to have significant association (p=0.054) with heroin dependence compared to the controls who had the A-T-G haplotype.…”
Section: Discussionmentioning
confidence: 96%
“…Single nucleotide polymorphisms in GRIN2A, have been extensively studied in recent years and results have revealed them to be possibly associated with drug addiction, including alcohol and heroin [13][14][15][16]. A variable GTn repeat in the 5'-regulatory region of N-methyl-Daspartate GRIN2A subtype was identified and significantly associated with alcohol dependence [14,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported an association of GRIN2A SNPs with heroin addiction (opioid dependence/OD) in a subsample of the current sample of African Americans (AA) (Levran et al, 2009). GRIN2A SNPs were also associated with OD in Han Chinese (Zhao et al, 2013; Zhong et al, 2014). GABRA2, GABRB3, GABRG2, and GAD1 SNPs were associated with OD in different populations (Loh et al, 2007; Enoch et al, 2010; Wu et al, 2012; Chen et al, 2014; Li et al, 2014; Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%